Authority Architecture And Architecture Criticism - Abbas, Sana Sati; Al-Dahui, suha Hassan (Iraqi Journal of Architecture and Planning)
Many ol criticism studies have focused on the concept of aurhority . These studies vary in their intentions, about the type of authority , according to their theoretical criticism direcrions. Also they varied in their disciplines, from lhe attention to the author, to co,nplete care to the text; eventually they transferred to the reader in thc last decade of the t ’entieth century .The research problem rvas "There is no conrprehensive image about the concept ofauthority in Architecture and specially in Academic architectural criticisnr". This study aims to define the specialty of authority in architecture and architectural criticisnr .The research hl,pothesis rvas " the authority in architecture is convenient have rnultiple resources ,meanings ,and disciplines of enfolding. tt is appear in the text exhibited to criticism through external items expresses the era and the rules of art. The methodology of the research is based on(theoretical study rvhich defines the theorctical framework for authority concept in architecture and architectural criticisrn in general and practical study rvhich investigated a group of academic critics, about the item ofthe framervork .The results obtained are analyzed to reach to the conclusions about the lraqi specialty ofauthority in architeclure and architectural criticism .Research findings u,as (rhe authority in architecture and criticism is convenient, its resource is the text, includes many meaning. the most lamous is the creativity . the elfects and the superiority .l he authority emerges in exhibitions, local and international competitions, and in the students producls .The authority depends on some means, the most famous are .the designers continuous encouragement .grades gir en . and the explanation. in order to produce products responding to the era , through dealing u,ith rhe design process, and the context used).